Exploring agricultural vocational pedagogy in Uganda: students' experiences. (2nd September 2019) - Jjuuko, Robert; Tukundane, Cuthbert; Zeelen, Jacques
ABSTRACT: Increasingly studies claim that building young people's vocational interest in agriculture, as a sector of meaningful employment, is a central dilemma of Africa's education and labour market systems. With Ugandan students' voices, this article examines some of the methodological dilemmas of agricultural education and training. The article draws from evidence generated through a qualitative case study of a public agricultural college. We undertook the study in line with our conceptual argument for mainstreaming young people's voices in the search for solutions to improve agricultural education practice. The study explored and analysed students' experiences and perceptions of the college's vocational pedagogy. Findings that uncover weak agricultural vocational pedagogy at the case study college are analysed and discussed to inform our recommendation for the embedding of craftsmanship virtues in vocational education practice to optimise students' achievement.